Algorithmic work coordination and workers' voice in the COVID-19 pandemic: The case of Foodora/Lieferando. (1st January 2021) - Schreyer, Jasmin
Abstract : The COVID-19 pandemic exacerbates the conflictual nature of work in the digital platform economy as if it were ignited under a magnifying glass. In this context, this article focuses on the logic of control of algorithmic labour coordination, adopting a qualitative case study approach. In a situation in which the technical infrastructure of online platforms generally impedes labour protests, it examines the case of Lieferando (formerly Foodora) in Germany, where, unusually, the on-demand workforce is employed. It concludes that in this situation, the algorithmic management of Lieferando facilitates labour protests because of a lack of communication between employer and worker. Furthermore, in the COVID-19 pandemic, institutionalised relationships function as a countervailing power to that of the employer, forcing it to act.